2018
DOI: 10.1016/j.nicl.2018.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific hippocampus volume changes in obstructive sleep apnea

Abstract: IntroductionObstructive sleep apnea (OSA) patients show hippocampal-related autonomic and neurological symptoms, including impaired memory and depression, which differ by sex, and are mediated in distinct hippocampal subfields. Determining sites and extent of hippocampal sub-regional injury in OSA could reveal localized structural damage linked with OSA symptoms.MethodsHigh-resolution T1-weighted images were collected from 66 newly-diagnosed, untreated OSA (mean age ± SD: 46.3 ± 8.8 years; mean AHI ± SD: 34.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 102 publications
3
48
2
Order By: Relevance
“…The limited histological evidence available from previous studies suggest amygdala and hippocampus are not spared from the disease process, in that they exhibit typical hallmarks of DM1 including neurofibrillary tangles [49,57]. Interestingly, sleep disordered breathing has been linked to both regional increases and decreases in hippocampus volume in non-DM1 subjects, held to represent the acute and chronic effects of hypoxia respectively [58]. Further, emerging evidence suggests a functional link between amygdala and control of respiration, with stimulation of the amygdala seen to induce apnea [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited histological evidence available from previous studies suggest amygdala and hippocampus are not spared from the disease process, in that they exhibit typical hallmarks of DM1 including neurofibrillary tangles [49,57]. Interestingly, sleep disordered breathing has been linked to both regional increases and decreases in hippocampus volume in non-DM1 subjects, held to represent the acute and chronic effects of hypoxia respectively [58]. Further, emerging evidence suggests a functional link between amygdala and control of respiration, with stimulation of the amygdala seen to induce apnea [59].…”
Section: Discussionmentioning
confidence: 99%
“…Further, respiratory function was not specifically assessed as part of the present study. Sleep-disordered breathing is common in DM1 [66], and has been linked to various structural brain changes in other patient populations [58,67,68], therefore detailed phenotyping of respiratory function including sleep studies should be considered as part of future neuroimaging work. Finally, the clinical impact of the structural changes identified were not explored as part of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to an interpretation bias and is explained by the fact that diagnoses in females are often under evaluated 52 and that the prevalence of OSAS is higher in males 53 . Nevertheless, studies have shown a gender influence, such as on hippocampal volume in OSAS 23 or greater cortical lesions in women with OSAS 54 . Consequently, sex ratio is a point that will have to be taken into account later on.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the imaging data showed that brain regions near the hippocampus had a volume that could either be increased or decreased. The explanation for an increased volume would be inflammation and activation of glial cells, while a decrease would suggest cell loss leading to neurodegenerative damage 23 . In addition, other studies described a decrease in OSA patients in entropy measurement that indicates an acute change in cerebral tissue and links it to the rupture of the BBB 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that sex influences all levels of brain in the extension of brain damages, mechanisms of damages, behavioral outcomes, and treatment efficacies in the neonatal hypoxic-ischaemic models [13][14][15]. Sex-specific cerebral cortices, moleculars, densities of nerve cells, neuroplasticities, iron contents, and cerebral hemodynamic changes were also found in the hypoxic populations [16][17][18]. Clinical data and animal studies confirmed sex differences in hypoxic-ischaemic outcomes, including emotions [19][20][21], cognitions [22], and attention domains.…”
Section: Introductionmentioning
confidence: 93%